Підготовка студентів педагогічних спеціальностей до організації ефективної міжкультурної комунікації здобувачів початкової освіти - Васютіна Тетяна; Tetiana Vasiutina (Видавництво «Код», 2025)
Резюме. У статті розкрито сутність поняття «міжкультурна комунікація» та описано підходи до підготовки майбутніх учителів до її організації з учнями. Встановлено, що результативність її формування у студентів забезпечується: інтеграцією культурознавчого компоненту у зміст нормативних та вибіркових дисциплін; використанням автентичних матеріалів, що відображають різноманіття культур (народні пісні, казки, прислів’я, обряди, гастрономічні традиції); застосуванням інтерактивних методів навчання, зокрема рольових ігор, дебатів, ситуаційного моделювання, що стимулюють комунікативну взаємодію між майбутніми учителями і готують їх до організації цієї діяльності з учнями; організацією проєктів у межах формальної, неформальної та інформальної освіти (міждисциплінарних проєктів, під час педагогічної практики, етнокультурних фестивалях, волонтерських ініціативах, заходах під час внутрішньої академічної мобільності).

Abstract. The article presents a theoretical and methodological analysis of the problem of developing the capacity of future primary school teachers to organise effective intercultural communication among pupils in a multicultural educational environment, taking into account the national context (internal and external migration, the integration of internally displaced persons into new territorial communities, and the multicultural specificity of certain regions). The concept of intercultural communication is defined as an integrative professional competence encompassing the process of mutual understanding and interaction between representatives of different cultural communities, founded on tolerance, empathy, reflective thinking, and respect for the value systems of communicants. Both national and international research on the issue has been analysed, demonstrating that the effectiveness of such training depends upon the creation of a developmental educational environment within universities, where intercultural communication functions not only as a substantive component of educational and professional programmes but also as a mode of organising partnership-based interaction among all participants in the educational process. It has been established that the success of this approach is ensured through: the integration of cultural studies into the content of compulsory and elective disciplines; the use of authentic materials reflecting cultural diversity (folk songs, fairy tales, proverbs, rituals, gastronomic traditions); the application of interactive teaching methods, particularly role-play, debates, and situational modelling, which stimulate communicative interaction among future teachers and prepare them to organise similar activities with pupils; and the implementation of projects within formal, non-formal, and informal education (interdisciplinary projects, teaching practice, ethnocultural festivals, volunteer initiatives, and events conducted within internal academic mobility programmes).
Preparing students of pedagogical specialities for organising effective intercultural communication among primary school pupils
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: майбутні вчителі початкової школи; молодші школярі; багатокультурне середовище